Discharge outcome analysis of 1089 transgender young people referred to paediatric endocrine clinics in England 2008–2021. Issue 11 (18th July 2022) - Butler, Gary; Adu-Gyamfi, Kirpal; Clarkson, Kerry; El Khairi, Ranna; Kleczewski, Sara; Roberts, Alice; Segal, Terry Y; Yogamanoharan, Karththeepan; Alvi, Sabah; Amin, Nadia; Carruthers, Paul; Dover, Stacey; et al.
Abstract : Introduction: The destination of transgender and gender variant young people referred by the National Health Service (NHS) Gender Identity Development Service (GIDS) to, and discharged from the two English paediatric endocrine liaison clinics is not known. Methods: 1151 young people referred after full assessment by the GIDS; 827 to University College London Hospital since 2008; 324 to Leeds Children's Hospital since 2013. Discharge categorisation was by agreed criteria. Eleven emigrated and 51 self-discharged. 1089 had known outcomes. Results: 999/1089 (91.7%) continued identifying as gender variant. 867/999 (86.8%) were discharged to adult gender identity clinics (GICs). 166/867 (19.1%) of these were <16 years and 701/867 (80.9%) ≥16 years at initial endocrine referral. No sex differences were seen. 38/999 (3.8%) opted for non-NHS services. 90/1089 ceased identifying as gender variant. In 32/1089 (2.9%), this was subsequent to their first clinic appointment. 58/1089 (5.3%) stopped treatment either with the gonadotropin releasing hormone analogue (GnRHa) or gender-affirming hormones (GAH) and reverted to their birth gender: <16 years (20/217; 9.2%); ≥16 years (38/872; 4.4%). Subdividing further, 16/217 (7.4%) <16 years ceased GnRHa and 4/217 (1.8%) after GAH. Of those ≥16 years, 33/872 (3.8%) ceased GnRHa and 5/872 (0.6%) GAH. Conclusions: At discharge, 91.7% continued as transgender or gender variant, 86.8% sought ongoing care through NHS GICs. 2.9% ceased identifying as transgender after an initial consultation prior to any endocrine intervention and 5.3% stopped treatment either with GnRHa or GAH, a higher proportion in the <16 year compared with the ≥16 year groups. Abstract : This paper reports post-discharge outcomes of a large national cohort of transgender and gender variant young people who were referred by the NHS Gender Identity Development Service (GIDS) to, and discharged from, the two English NHS paediatric endocrine liaison centres clinics.